Is perfectionism associated with academic burnout through repetitive negative thinking? - Garratt-Reed, D.; Howell, Jennifer; Hayes, L.; Boyes, Mark (PeerJ, Ltd., 2018)
Academic burnout is prevalent among university students, although understanding of what predicts burnout is limited. This study aimed to test the direct and indirect relationship between two dimensions of perfectionism (Perfectionistic Concerns and Perfectionistic Strivings) and the three elements of Academic Burnout (Exhaustion, Inadequacy, and Cynicism) through Repetitive Negative Thinking. In a cross-sectional survey, undergraduate students (n=126, Mage= 23.64, 79% female) completed well- validated measures of Perfectionism, Repetitive Negative Thinking, and Academic Burnout. Perfectionistic Concerns was directly associated with all elements of burnout, as well as indirectly associated with Exhaustion and Cynicism via Repetitive Negative Thinking. Perfectionistic Strivings was directly associated with less Inadequacy and Cynicism; however, there were no indirect associations between Perfectionistic Strivings and Academic Burnout operating through Repetitive Negative Thinking. Repetitive Negative Thinking was also directly related to more burnout Exhaustion and Inade- quacy, but not Cynicism. It is concluded that future research should investigate whether interventions targeting Perfectionistic Concerns and Repetitive Negative Thinking can reduce Academic Burnout in university students.